Uma construção de fatos e palavras: Cícero e a concepção retórica da história A construction of deeds and words: Cicero and the rhetorical conception of history - Felipe Charbel Teixeira (Varia História, 2008)
O artigo analisa a concepção retórica da história tal qual exposta por Cícero no segundo livro do diálogo De Oratore. Argumenta-se que o entendimento da história como uma construção de fatos e palavras tanto enfatiza seu caráter retórico quanto o compromisso da história com a verdade, sendo que, para Cícero somente um orador prudente pode se mostrar capaz de produzir um texto digno de ser chamado "história", texto que simultaneamente deleite e produza em seus leitores e ouvintes lições de virtude. The article analyses Cicero's rhetorical conception of historical writing, as exposed in De Oratore's second book. One argues that Cicero's comprehension of history as a construction of deeds and words emphasizes both its rhetorical character and its commitment to truth. According to Cicero only a prudent orator is able to create a text which may be called "history", a text which simultaneously delights and produces lessons of virtue to his readers and listeners.